Trendlerin ve dönemsel değişimlerin ürünlerin strüktürel yapılarına etkilerinin kullanıcı elektroniği sektöründe incelenmesi - Devrim, Özlem (My University, 2012)
Trendler, moda, tasarım disiplinleri ve sanat ile yakından ilgilidir. Bu disiplinler içinde sıklıkla moda alanı içerisinde oldukça fazla kullanılan “trend” kelimesi günlük yaşam dilinde anlamı dışında da kullanılmakta, kısa dönemli moda akımları ile karıştırılmaktadır. Trendler, Günlük ve geçici olanın tam aksine fütüristik yaklaşımlar ile derinleştirilmeli, algılanabilmesi için gelecekbilim araştırma yöntemleri kullanılmalıdır. Toplumların kültürlerinin birbirlerini etkilediği ve birbirinden beslendiği bir gerçektir. Trendler de birbirinden beslenmiş ve birbirine sıkı sıkıya bağlı bu kültürlerin değişiminde önemli bir yer tutmaktadır. Teknolojik gelişmeler 2000’li yılların başlarından günümüze değin gitgide artan bir ivme ile yenilikleri beraberinde getirmektedir. Özellikle elektronik ürünler üzerinde takip edilemez bir değişim rüzgarı esmekte, trendlerin etkilediği şaşırtıcı farklılıkta seçimler çevremizi kuşatmaktadır. Araştırmada da, 2000-2011 döneminin kullanıcı elektroniği özelinde trend raporu çıkartılmıştır. Araştırma bir bakıma, kullanıcı elektroniği özelinde, geleceği kapsayan uzgörüler kanalına bir giriş niteliğindedir.

Trends are closely connected to fashion, design disciplines and arts. The term “Trend”, having been widely used especially in the discipline of fashion out of the others defined above, which is rather suspect in terms of it actual meaning, is also widely used in day-to-day life of the ordinary folk in a wrong manner, and therefore often confused with “short term trends in the world of fashion”. However, “trends”, as I would prefer to define it, are not suppose to be daily and temporary / provisional things and/ or acts, but the very things and/ or acts that are to be further deepened through the implementation of futuristic approaches and in doing so, research methods of futuristic science must be used for it to be perceived correctly. It is a fact that cultures of the societies have always been influenced one another and so interacted in due course. Indeed, trends, too, have always been influenced one another and played an important role in transformation of cultures regardless of how closely they may interwoven to each other. Since the turn of the new millennium, many new, innovative products have been designed at an ever increasing rate thanks to latest technological developments. A trend report on the use of consumer electronics from 2000 to 2011 is also included in the research. In some sense, the said research also sheds a light on the actual course which the consumer electronics might take into the future. .
Keywords: Endüstri Ürünleri Tasarımı